Multi-pulse triboelectric nanogenerator based on micro-gap corona discharge for enhancement of output performance. (1st April 2022) - Wang, Ru; Cui, Juan; Liu, Yabing; Liu, Dan; Du, Chunhui; Yan, Shubin; Zheng, Yongqiu; Xue, Chenyang
Abstract: Triboelectric nanogenerator (TENG), which can convert all forms of mechanical energy into electricity, has been hailed as one of the economical ways to harvest energy. However, the development and application of TENG are limited due to its low output power. Although it is found that the power of TENG can be increased by introducing corona discharge, there are few studies on the influential factors of TENG based on corona discharge. In this paper, the multi-pulse triboelectric nanogenerator (MP-TENG) with enhanced output power is proposed by controlling the negative corona discharge through the integration of TENG and the micro-gap. The experimental results show that Voc, Isc and Qsc are improved 154%, 725% and 3025% respectively. Moreover, the highest power growth rate of 646% can be achieved under a low frequency. The MP-TENG demonstrates a superior output performance that the charging time of 100 μF capacitor to 3.5 V shortens by 1/5 and 12 parallel LED panels (240 lamp beads) can be lit up, which presents a great potential in practical application and plays a guide role in introducing corona discharge into the TENG. Graphical abstract: Image 1 Highlights: MP-TENG induces the corona discharge through the micro-gap, which significantly improves its output performance. Highest power growth rate can be obtained at low frequency breakdown. The conditions for inducing corona discharge successfully include voltage amplitude and pulse width.